Postmodern Fairy Tales : Gender and Narrative Strategies. (University of Pennsylvania Press, 1999)
"An extraordinary book, and a 'first' on the topic. ... Bacchilega has a remarkable capacity to reveal the intersections of folklore, literature, and film. Her interpretations of classical folk-tale types and their postmodern revisions ... are stunning."--Jack Zipes, University of Minnesota.